Implementasi Financial Technology Dalam Pengelolaan Keuangan Kafe Kopi Kampus Antirogo - Fauziyah Azzahro; Venantya Asmandani; Rina Dwi Desianti; Nabila Novareta (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2026)
The development of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt more effective and integrated business management systems, particularly in financial and human resource management. Kafe Kopi Kampus Antirogo is one MSME that has seen an increase in the number of visitors since its establishment in 2022, but still faces problems in financial recording and employee attendance, which are done manually and are not yet integrated. This community service activity aims to improve business management effectiveness through training and the implementation of an integrated financial technology application. The methods used include initial discussions with partners, Focus Group Discussions (FGD) to identify needs, application development, system usage training, as well as mentoring and evaluation. The developed application allows business owners to access financial reports in real-time and monitor business operations directly, as well as providing a digital attendance system for employees. The evaluation results show measurable improvements, with financial recording accuracy increasing from 60% to 90% after implementation. Transaction recording time was reduced by about 40%, and attendance reporting errors decreased by almost 50%. The implementation of financial technology has proven to improve operational efficiency, transparency, and the quality of data-driven decision-making at Antirogo Campus Coffee Shop.